IDEALISASI SIFAT ALTERNATIF DALAM PENYELESAIAN SENGKETA MELALUI MEDIASI - Sugianto, Fajar; Simeon, Felicia Christina; Wibowo, Dea Prasetyawati (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Abstract The purpose of the research is to make a law comparison related to disputes by mediation. This research is using normative method with empirical approach. Through this research the researcher offers an interesting development of dispute resolution through mediation where mediation is no longer used to settle disputes outside the court, but in it’s development mediation is also used to settle disputes in court, known as mediation in court. This phenomenon first developed in developed countries like United States before finally developed in Indonesia. Every people have their own various ways to obtain agreement in the case process or to resolve disputes and conflicts. One way to resolve disputes is through mediation. Mediation clearly involves third parties (both individuals and in the form of an independent institution) that are neutral and impartial, who will take a role as a mediator. The basic principles in mediating dispute resolution both in court and outside the court are still being carried out, such as the principles of confidentiality, neutrality, empowerment of the parties, and mediation results are sought to reach a win-win solution agreement.Keywords: dispute; mediation; mediatorAbstrak Tujuan penelitian yaitu melakukan perbandingan hukum terkait penyelesaian sengketa dengan cara mediasi. Menggunakan metode penelitian normatif dengan pendekatan empiris. Melalui penelitian ini peneliti menawarkan perkembangan yang menarik dari penyelesaian sengketa melalui mediasi dimana mediasi tidak lagi semata-mata digunakan untuk menyelesaikan sengketa di luar pengadilan saja, akan tetapi dalam perkembangannya mediasi juga digunakan untuk menyelesaikan sengketa di pengadilan, yang dikenal dengan mediasi di pengadilan. Fenomena ini lebih dulu berkembang di Negara-negara maju seperti di Amerika Serikat sebelum akhirnya berkembang di Indonesia. Setiap masyarakat memiliki berbagai macam cara untuk memperoleh kesepakatan dalam proses perkara atau untuk menyelesaikan sengketa dan konflik. Salah satu cara penyelesaian sengketa yang ada adalah melalui mediasi. Mediasi jelas melibatkan pihak ketiga (baik perorangan maupun dalam bentuk suatu lembaga independen) yang bersifat netral dan tidak memihak, yang akan berperan sebagai mediator. Prinsip-prinsip dasar dalam penyelesaian sengketa secara mediasi baik di pengadilan maupun di luar pengadilan tetap dijalankan, seperti prinsip kerahasian, netralitas, pemberdayaan para pihak, dan hasil mediasi diupayakan mencapai kesepakatan win-win solution.Kata kunci: mediasi; mediator; sengketa